A temperature-controlled mid-wave infrared polarization radiation source with adjustable degree of linear polarization. (15th June 2022) - Sun, Zunyi; Jin, Weiqi; Kang, Guoguo; Li, Li; Yang, Jianguo
Highlights: A temperature-controlled midwave IR polarization radiation source is designed. The radiation source can be readily adjusted by changing the temperature. A method for measuring the DoLP of radiation source is disclosed. The DoLP of radiation source exhibits the large dynamic range and high accuracy. Abstract: This paper proposes a temperature-controlled mid-wave infrared polarization radiation source with adjustable degree of linear polarization (DoLP), referred to as TMPSD, which will be useful for the polarization performance measurements of the thermal polarization imaging systems. The main parts of the TMPSD are a standard blackbody source, a variable temperature cell holder and a mid-wave infrared polarizer placed in it. The experimental results show that when the temperature range of the blackbody source changes between 20 °C and 100 °C, and that of the polarizer between −120 °C and 20 °C, the DoLP of the radiation emitted from the TMPSD is 0.2683–0.9072 in the 3.0–5.2 μm bandwidth. The TMPSD exhibiting the large dynamic range and high accuracy can be readily adjusted. It is expected that the proposed TMPSD will effectively improve the quantitative accuracy of infrared polarization imaging systems during performance calibration and testing of mid-wave infrared polarization imaging systems.